Community participatory techniques: Have such techniques been able to make an impact - Sulania, Anika; Rasheed, Nazish (Indian Journal of Community Health, 2014)
India remains far from attaining the goal of health for all proposed by WHO during 1977 to be achieved by 2000. According to WHO, Alma-Ata Declaration of 1978, “The people have a right and duty to participate individually and collectively in the planning and implementation of their health care” [1]. The approach was clearly targeted for communities to achieve a level of health which would permit all individuals to lead a socially useful and economically productive life through primary health care approach. With this statement the focus started shifting towards community development through their participation.